2014
DOI: 10.1055/s-0034-1383300
|View full text |Cite
|
Sign up to set email alerts
|

Optimierung der Visualisierungstechnik für Strahlenverläufe durch Intraokularlinsen zur Charakterisierung multifokaler Abbildungseigenschaften von Fresnel-Zonenplatten

Abstract: The utilisation of the diffractive properties of Fresnel zone plates offers the possibility of intraocular lens designs with multiple foci. Such intraocular lenses can be manufactured by two-photon polymerisation (2PP). This paper explains the underlying concept and shows the principles for visualisation of the focus properties of such implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…In this study, we implemented the imaging technique [20] to assess the ray propagation and forward light scatter of opacified IOLs and a clear IOL, and we found a good agreement between the qualitative (imaging technique) and quantitative (straylight) measurements. Previously, a similar experimental setup was utilized to understand the fundamental properties of IOLs [25][26][27]. Terwee et al demonstrated the functional differences between diffractive and refractive multifocal IOLs by using monochromatic green light and United States Air Force target projections [25], while Eppig et al used a different medium, namely ouzo, to demonstrate the halo effects of monofocal and multifocal lenses [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we implemented the imaging technique [20] to assess the ray propagation and forward light scatter of opacified IOLs and a clear IOL, and we found a good agreement between the qualitative (imaging technique) and quantitative (straylight) measurements. Previously, a similar experimental setup was utilized to understand the fundamental properties of IOLs [25][26][27]. Terwee et al demonstrated the functional differences between diffractive and refractive multifocal IOLs by using monochromatic green light and United States Air Force target projections [25], while Eppig et al used a different medium, namely ouzo, to demonstrate the halo effects of monofocal and multifocal lenses [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sitnikova et al found that an ouzo-water-emulsion may stay stable for several months [23] and does not suffer from photodegradation, which makes it a useful test medium. Other dilutions like milk powder [18] or fluorescein [19, 20], which have been used in previous publications, may degrade or segregate from water over time. However, the image quality was impaired by Schlieren and frequent bright spots/stripes originating from saline crystals (as they were seen in pure BSS and fluorescein in BSS as well, compare Figure 9), dust, or oil droplets.…”
Section: Discussionmentioning
confidence: 99%
“…Other visualization media, e.g., fluorescent dyes such as fluorescein, have the advantage of less Schlieren and scattering effects when they are used in fluorescent mode only (compare Figures 9 and 10) but they are highly dependent on the wavelength of the excitation light. Reiss et al and Son et al [19, 20] used fluorescein in combination with a green laser which does not address the full quantum efficiency of the fluorescein (Figure 11). Therefore higher laser intensity is required which also makes scattered light visible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations